Ornithine transcarbamylase deficiency of a male newborn with fatal outcome - Hartung, Benno; Hinderhofer, Katrin (International journal of legal medicine, 2016)
Ornithine transcarbamylase deficiency (OTCD) is the most common malfunction of ureagenesis. The case of a male newborn who died at the age of 2 days for clinically unclear reasons is presented. The post-mortem routine and esoteric testing methods that finally led to the diagnosis of a fatal case of OTCD are outlined here.
Gesehen am 29.10.2019